ANALISIS KEARIFAN LOKAL DALAM BUDIDAYA PADI RAMAH LINGKUNGAN DI KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Wahyudi1, Riyon Eka; Sayamar, Eri; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to know the local wisdom in Kelayang Sub-district Indragiri Hulu Regency. Kelayang Sub-district is one of the rice producing areas in Indragiri Hulu Regency. In this research the data collection method used is survey method with the help of questionnaires to 30 respondents in Kecamatan Kelaynag, the method of analysis used is the SWOT method, this method is used to see the local wisdom in Kelayang sub - district. In the SWOT analysis the data collected is internal data, covering the strengths and weaknesses owned by a local wisdom and external data, covering the pelung and threats own by a local wisdom. so to see the relevance of the local wisdom, then is made SO strategy, WO strategy, WT strategy and WO strategy . The result of this study is, Existing local wisdom is, praying from the process of land clearing to harvesting, making offerings, Mutual cooperation, using traditional tools, and forbidden to say dirty. while local wisdom that is not exist is to determine a good day, prohibited Harvest on Friday and ask permission to ghost before taking the rice. Keyword : Local wisdom,kelayang,Rice,SWOT